2004
DOI: 10.1590/s0103-64402004000200006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the thermal alterations on the root surface during preparation with different Ni-Ti rotary instruments

Abstract: The present study evaluated, in vitro, the temperature alterations on the external root surface during instrumentation with four different rotary systems. A total of 20 extracted human maxillary lateral incisors were instrumented using either the ProFile, MicroMega, Quantec or K3 systems and the thermal alterations on the root surface were recorded by means of three thermocouples attached to the coronal, middle and apical portions of the root. Mean temperature increases no higher than 0.4 degrees C +/- 1.0 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…Several methods have been investigated to measure temperature changes. [15,28,29] Noncontact infrared thermometers measure the temperature in a short period of time and do not require other instruments or contact during the measurement. In addition, they do not cause infection, are less costly and do not require any preparation prior to the measurement.…”
Section: Sd=standard Deviation; Se=standard Error; Ci=confidence Intementioning
confidence: 99%
“…Several methods have been investigated to measure temperature changes. [15,28,29] Noncontact infrared thermometers measure the temperature in a short period of time and do not require other instruments or contact during the measurement. In addition, they do not cause infection, are less costly and do not require any preparation prior to the measurement.…”
Section: Sd=standard Deviation; Se=standard Error; Ci=confidence Intementioning
confidence: 99%
“…It has been stated that a TR over 10°C on the RS of the tooth during endodontic treatment may be harmful for the cementum, periodontal ligament, and alveolar bone tissues. 1316 Therefore, the temperature level reached during endodontic treatment is important for the prognosis of the related tooth.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that a TR over 10°C on the RS of the tooth during endodontic treatment may be harmful for the cementum, periodontal ligament, and alveolar bone tissues. [13][14][15][16] Therefore, the temperature level reached during endodontic treatment is important for the prognosis of the related tooth. In this study, the TR observed on the RS during the endodontic retreatment of RCs filled with AH Plus or CeraSeal and gutta-percha using Resiproc or WOG was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…When 20 extracted human maxillary lateral incisors were instrumented using either the ProFile, MicroMega, Quantec, or K3 systems and the temperature changes on the root surface in the coronal, middle, and apical portions of the root were recorded, the mean temperature increase was 0.4°C ± 1.0°C (ProFile system), which indicates that these instruments are safe for the surrounding periodontal tissues .…”
Section: Temperature Increasementioning
confidence: 97%